2002
DOI: 10.1021/la011663c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Degradation of Polyester Blend Monolayers at the Air/Water Interface:  Effects of a Slowly Degrading Component

Abstract: The hydrolytic behavior of monolayers of biodegradable [poly(l-lactide)/poly( -caprolactone)] (l-PLA/ PCL) blends spread at the air/water interface is studied to identify the relative rate of hydrolytic degradation of each component when exposed to a basic subphase. As the hydrolysis time increases, the isotherm recorded from (l-PLA/PCL) blend monolayers was found to be similar to that of PCL homopolymer; this is likely due to the preferred hydrolysis of l-PLA. The rate of hydrolysis was recorded by a change o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…The influence over the degradation process strongly depends on the hydrophilicity/hydrophobicity and dispersion of the nanoparticles. Moreover, a delayed biodegradability due to the improved barrier properties of the nanomaterials was previously observed, which could hinder the water diffusion through the bulk [42]. The study of the disintegration in composting conditions of PLA and PLA bionanocomposites was carried out to evaluate the effect of the addition of LNPs and processing methods on the disintegrability properties of the PLA matrix.…”
Section: Disintegrability In Compost Of Pla Bionanocompositesmentioning
confidence: 99%
“…The influence over the degradation process strongly depends on the hydrophilicity/hydrophobicity and dispersion of the nanoparticles. Moreover, a delayed biodegradability due to the improved barrier properties of the nanomaterials was previously observed, which could hinder the water diffusion through the bulk [42]. The study of the disintegration in composting conditions of PLA and PLA bionanocomposites was carried out to evaluate the effect of the addition of LNPs and processing methods on the disintegrability properties of the PLA matrix.…”
Section: Disintegrability In Compost Of Pla Bionanocompositesmentioning
confidence: 99%
“…On the other hand, Mallard e et al [239] reported that oligomeric PDLLA (M n ¼ 1100 g/mol) enhanced the alkaline hydrolytic degradation of poly(3-hydroxyoctanoate). Lee et al [14,236] found that the dilution effect of slowly degrading PCL on rapidly degrading PLLA increased the alkaline hydrolytic degradation of PLLA/PCL blend monolayers with PLLA contents below 50%. Similarly, regarding bulky PLLA-based blends, the incorporation of PCL or P(LLA-co-CL) increased the total NHD of the blends as traced by molecular weight, and the enhancing effect was higher for P(LLA-co-CL) [27,237].…”
Section: Highly Ordered Structuresmentioning
confidence: 99%
“…[10][11][12][13][14][15] The low molecular weight oligomers and monomers generated by hydrolysis dissolve into water. This would result in a change in the occupied area if the monolayer is maintained at a constant surface pressure.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior implies that the carboxyl acid group, not the alcohol group generated by the chain cleavage of ester bond is mainly related to the molecular loss likely due to the formation of carboxyl acid salts with sodium ion and then the increase of the solubility into subphase. [13][14][15] Therefore, the diffusion of acid fragments away from the reacting monolayer may well be the rate determining step. Figure 2 shows the surface pressure-area isotherms for dl-PLA monolayers on subphase of pH 10.5 measured with different pause times of 1 and 2 hr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation